2004
DOI: 10.1136/gut.2003.036160
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, controlled, double blind, escalating dose study of alicaforsen enema in active ulcerative colitis

Abstract: Objective: To evaluate the safety and efficacy of an enema formulation of alicaforsen, an antisense inhibitor of intercellular adhesion molecule, after 1, 3, and 6 months. Methods: This was a randomised, placebo controlled, double blind, escalating dose multicentre study in 40 patients with mild to moderately active distal ulcerative colitis (disease activity index (DAI) 4-10). Patients were assigned to four dosing cohorts of 10 patients each (eight active, two placebo). Each patient received 60 ml of alicafor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(115 citation statements)
references
References 21 publications
2
109
0
1
Order By: Relevance
“…Our results with a clear and fast reduction of clinical disease activity (Mayo score -27%, partial Mayo score -60%, and 6-point symptom score -62%) are consistent with those of the open label study by Miner et al [27] and the small randomized-controlled trial by van Deventer [28]. The clinical improvement rate of 83.3% (10 out of 12) is comparable to that of Miner et al [27] (clinical improvement in 12/15 patients [80%]).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results with a clear and fast reduction of clinical disease activity (Mayo score -27%, partial Mayo score -60%, and 6-point symptom score -62%) are consistent with those of the open label study by Miner et al [27] and the small randomized-controlled trial by van Deventer [28]. The clinical improvement rate of 83.3% (10 out of 12) is comparable to that of Miner et al [27] (clinical improvement in 12/15 patients [80%]).…”
Section: Discussionsupporting
confidence: 79%
“…Nonetheless, a prolonged clinical response was observed in both trials with a significant reduction in dis-Dig Dis 2018;36:123-129 DOI: 10.1159/000484979 ease activity at weeks 18 and 30 compared to placebo (51 vs. 18% and 50 vs. 11%) and a significant longer duration of response compared to mesalazine (146 vs. 54 days). In a smaller randomized controlled trial, van Deventer et al [28] showed both a short-term and long-term benefit from alicaforsen enema treatment: disease activity was reduced by 78% at day 29 and by 68% at 3 month compared to a placebo response of 28 and 11.5% respectively. Given the fact that the half-life period of alicaforsen is only 24 h, these findings have led to the concept of a disease-modifying ef- fect.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, antisense oligonucleotides represent a strategy for modulating cell adhesion by inhibiting the expression of adhesion molecules. Clinical trials of ICAM-1 antisense oligonucleotides have already been started in human inflammatory bowel diseases (58,59) and rheumatoid arthritis (60). Until now, few therapies have proved to be effective for SSc in control studies.…”
Section: Discussionmentioning
confidence: 99%
“…Initial positive results in CD patients reported in a pilot study were not confirmed in two subsequent placebo controlled trial (45)(46)(47). Instead in a placebo controlled trial with ISIS 2302 in enema formulation showed significant improvement in 40 patients with distal UC (48). In a phase 2, dose-ranging, double-blind, placebo-controlled study, 112 patients with mild-moderate left-sided UC received one of four ISIS 2302 enema regimens or placebo daily for 6 weeks (49).…”
Section: Selective Adhesion Molecule Inhibitorsmentioning
confidence: 93%